2008
DOI: 10.1590/s0101-20612008000100027
|View full text |Cite
|
Sign up to set email alerts
|

Aplicação de lipase e monoglicerídeo em pão de forma enriquecido com fibras

Abstract: O pão é o produto obtido pela cocção, em condições tecnologicamente adequadas, de uma massa fermentada, ou não, preparada com farinha de trigo e/ou outras farinhas que contenham naturalmente proteínas formadoras de glúten ou adicionadas das mesmas e água, podendo também conter outros ingredientes. A classificação "pão de forma" é atribuída ao produto obtido pela cocção da massa em formas, apresentando miolo elástico e homogêneo, com poros finos e casca fina e macia (BRASIL, 2006). Vários tipos de fibras podem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
13

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 24 publications
(36 reference statements)
1
6
1
13
Order By: Relevance
“…With respect to the whole grain bread samples, moisture values were slightly higher than those obtained by Gandra et al (2008), who studied bread containing wheat bran (20% flour basis) and found moisture contents of 34.13% and 31.55% on the first and seventh day of analysis, respectively.…”
Section: Physicochemical Analysescontrasting
confidence: 60%
See 1 more Smart Citation
“…With respect to the whole grain bread samples, moisture values were slightly higher than those obtained by Gandra et al (2008), who studied bread containing wheat bran (20% flour basis) and found moisture contents of 34.13% and 31.55% on the first and seventh day of analysis, respectively.…”
Section: Physicochemical Analysescontrasting
confidence: 60%
“…It has a blend of emulsifiers (calcium stearoyl-2-lactyl-lactate, polysorbate 80, and guar gum), which may have contributed to the increased volume, besides the a-amylase and other enzymes that may be present although they are not listed as ingredients. emulsifiers improve dough handling, increase loaf volume, improve the texture of the crumb, and improve shelf life (Moayedallaie et al, 2010;Gandra et al, 2008). The class and type of flour and the type and amount of fiber added may also affect the specific volume (Sluimer, 2005).…”
Section: Physicochemical Analysesmentioning
confidence: 99%
“….g -1 (Tabela 6). Gandra et al (2008) obtiveram valores de 3,77 e 4,40 cm 3 .g -1 em pães de fôrma enriquecidos com fibras e adicionados de lípase e monoglicerídeos. Em pães do tipo fôrma fortificados com ferro, Nabeshima et al (2005) relatam volume específico variando de 3,03 a 3,54 cm 3 .g -1 .…”
Section: Análise Sensorialunclassified
“…Nonetheless, these results did not affect the product quality since it was nutritionally enriched (Table 3). Today, consumers search for products that can offer health benefits, especially for natural additives, ingredients, and foods (Gandra et al, 2008).…”
Section: Evaluation Of Nutritional Potentialmentioning
confidence: 99%